Profit Analysis and Development Strategy of Beef Cattle Business of PT Riau Andalan Pulp and Paper Community Development Programme, Riau Province - Febrianto, Jeni; Ismail, Ujang Paman; Elinur, Elinur (SINTA Journal (Science, Technology, and Agricultural), 2024)
Riau Province is one of the potential areas for beef cattle business development. Basically, the purpose of a business is to make a profit so it is necessary to know what factors affect the profit of beef cattle business so that it can continue to improve the beef cattle business run by farmers. The objectives of the study were to determine the characteristics of farmers and their business profile, analysis of beef cattle business, factors affecting beef cattle business profits and beef cattle development strategies. Survey method was used in this study with stratifies sampling technique with a total of 74 respondents from each estate. Data analysis of business profit function using multiple linear regression analysis. Development strategy using SWOT analysis and QSPM matrix. The results showed that overall, the dominant age group was in the productive age range, the average education was elementary school, the number of family members was 3 people and business experience was 17.4 years.Â  Beef cattle business is still feasible. Variables that have a significant effect on the profit of beef cattle business are the selling price of males (P1), input costs of male feeders (r4), grass prices (r5), supplementary feed prices (r6), medical expenses (r7), business scale (x1), livestock mortality (x2) and pregnant cattle (x4). Strategies that can be done for the development of beef cattle business are maintaining product continuity by maintaining existing food sources and livestock populations, maintaining the area of feed areas and increasing crops for beef cattle forage, utilising technology for beef cattle cultivation in order to increase production, fairly easy maintenance, and increase farmers' interest, utilising technology in increasing business and marketing results and maintaining the quality of beef cattle provides a wide market space and consumers have more confidence in beef cattle products.